Designing Online Dictionaries of Economics: Two Opposing Views - Fuertes-Olivera, Pedro A. (HERMES - Journal of Language and Communication in Business, 2014)
This paper supports the argument that a dictionary of Economics in the broad sense of the word is any information tool that contains structured data - e.g. dictionary articles, outer texts, hyperlinks, etc. – which can be used for retrieving information on economic concepts, economic language, economic instructions, and/or economic operations. Some of these are on the Internet and are accessed by individuals for concrete consultation in one or more situations. This definition is based on the tenets of the Function Theory of Lexicography, the theoretical construction initiated at the Aarhus School of Business in the 1990s which has since worked on the theory and practice of dictionaries (Bergenholtz/Tarp 2002, 2003, 2004; Tarp 2008; Fuertes-Olivera/Tarp 2014). This has resulted in a specific approach to dictionary making, which is identifi ed in this chapter as a lexicography-based approach. On the other hand, some scholars espouse a different view, which is basically rooted in the theories and methods of (Applied) Linguistics (Rundell 2012a) and identified here as a linguistics-based approach. Both views are discussed and illustrated in relation to three specific issues: (a) the concept of a dictionary of Economics; (b) the sources of lexicographic data used in different dictionaries of Economics; (c) access to data and data presentation in several online dictionaries of Economics.